Processing and equipment of salted-shrimp manufacturing - Đặng Thiện Ngôn; Trần Quốc Hùng; Dương Bình Nam (Journal of Technical Education Science, 2012)
Shrimp, salt and chilli are abundant in the coastal areas of southwest Vietnam, and are easy to be processed. However, these sources have not yet been studied for making the products more valuable. This study attempted to investigate the processing and equipment of salted-shrimp manufacturing. The results showed that not only a new product was created but also the production efficiency and the living standard of Vinh Chau-Soc Trang people were improved. Moreover, it has given a chance for the local people to find a job. In addition, the product entirely met the required hygienic standard.